The prevalence of underweight, overweight and obesity in Bangladeshi adults: data from a national survey - Biswas, Tuhin; Garnett, Sarah P.; Pervin, Sonia; Rawal, Lal Bahadur (© 2017 Public Library of Science, 2018)
This article was published in the PLoS ONE [© 2017 Biswas et al. ] and the definitive version is available at: https://doi.org/10.1371/journal.pone.0177395 The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0177395